ADJUVANT CHEMOTHERAPY EFFECTIVENESS FOR І–ІІ STAGE NON-SMALL CELL LUNG CANCER (NSCLC) PATIENTS DEPENDING ON THE TUMOR MOLECULAR PROPERTIES - O. P. Kolesnik (European Scientific Journal, ESJ, 2014)
Adjuvant chemotherapy use on early stages non-small cell lung cancer patients remains the debatable issue. For individualization purpose of adjuvant chemotherapy administration it is possible to use molecular prognostic/predictive markers. The goal of our study was to investigate the adjuvant chemotherapy effectiveness on early stage NSCLC patients depending on the various molecular markers expression in primary tumor. Included in research are 254 patients with І–ІІ stage non-small cell lung cancer (NSCLC) that received institutional treatment in the department of thoracic surgery of Zaporizhyzhya Regional Clinical Oncologic Dispensary starting from June of 2008 up to December of 2012. For adjuvant chemotherapy administration individualization purpose the following molecular markers were used: Ki-67, CD31/CD34, Pan-Cytokeratin, Her-2/neu, p53, E-cadherin, EGFR. Low Кі-67, CD31/CD34, р53 expression level is a marker of adjuvant chemotherapy negative influence on early stage NSCLC patients survival rate. Alternatively, at high expression level of the said markers the adjuvant chemotherapy administration significantly improves examined patients survival rate. Pan-Cytokeratin indicates the presence of micrometastases in the lung root lymph nodes, and those are such patients, whose survival rate is improved by adjuvant chemotherapy conduction. Her-2/neu is the marker of tumor chemoresistance, more specifically, for patients with high expression level of such marker conducting of adjuvant chemotherapy is not appropriate, because this type of treatment does not improve survival at indicated marker characteristics. At the same time, low level of Her- 2/neu expression is a marker of chemosensivity and adjuvant chemotherapy conduction on such patients improves their survival rate. Significant predictive connection of E-cadherin EGFR expression level, high Her-2/neu expression and the absence of micrometastases is not established.